Diseases of the cervix – non-obvious consequences of pelvic floor muscle failure - Mekan R. Orazov; Liliia R. Toktar; Gulirano A. Karimova; Veronica Pak; Ksenia Li (Гинекология, 2021)
The literature review presents domestic and foreign data on the relationship between pelvic floor dysfunction (PFD) and cervical diseases found in PubMed, Scopus, Embase and eLibrary systems over the past 10 years. This relationship is mainly realized due to alterations in vaginal biocenosis as the earliest clinical manifestation of PFD. The article describes PFD prevalence, classification, and risk factors for PFD. It also describes main methods of treatment and their side effects. The article provides data on changes in the vaginal biocenosis in PFD. Attention is paid to the risk for cervical intraepithelial neoplasia and cervical cancer in PFD.